2021
DOI: 10.1111/add.15424
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of cannabis vaping videos on YouTube

Abstract: Background and AimsThere has been an increase in the potency of cannabis during the last two decades and adoption of a novel method of administration-vaping. YouTube, a social media platform, has become a popular source to access cannabis-related information. This study aimed to identify cannabis vaping YouTube videos from 2016 to 2020 and examine the themes and metrics. Design Cross-sectional sample of 200 YouTube videos. Setting YouTube, an on-line video sharing platform. Measurements Videos related to canna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…A codebook was developed based on themes generated from a random subset of 50 videos (Appendix S1) and then calibrated with existing analyses of cannabisrelated content on social media [22,24] to identify themes from similar analyses that may not have been generated from the subset. From this subset of videos, five initial themes were identified ('Humour/Entertainment', 'Informative', 'Experiences', 'Creativity' and 'Marketing').…”
Section: Coding Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A codebook was developed based on themes generated from a random subset of 50 videos (Appendix S1) and then calibrated with existing analyses of cannabisrelated content on social media [22,24] to identify themes from similar analyses that may not have been generated from the subset. From this subset of videos, five initial themes were identified ('Humour/Entertainment', 'Informative', 'Experiences', 'Creativity' and 'Marketing').…”
Section: Coding Proceduresmentioning
confidence: 99%
“…These themes were identified by describing the content and the main message of the videos within the subset to develop a thematic category. Novel themes that were not found in the analysis of the subset videos but would be of interest given the implications exposure to this content may have, were selected from content analyses of cannabis posts on video-based social media platforms [22,24]. Four themes ('How-To' [24], 'Lifestyle Acceptability' [22], 'Endorsements' [24] and 'Warning' [24]) were identified from existing cannabis content analysis literature.…”
Section: Coding Proceduresmentioning
confidence: 99%
“…All disagreements were resolved after discussion. The number of views and likes were used as a proxy for popularity 22 and these metrics were rounded by TikTok. The video themes and metrics were summarised using descriptive statistics.…”
Section: Coding Proceduresmentioning
confidence: 99%
“…Exposure to tobacco product marketing has been extensively identified as a marker of tobacco product use 12 46. Studies have shown that positively framed e-cigarette-related social postings are highly viewed, without age restrictions, on popular media among youth 44 47 48. Two competing explanations to the mediation result are (1) youth who use MTEP are perceiving more product marketing and (2) reduced danger perceptions could be an indicator rather than a result of higher propensity for tobacco use.…”
Section: Discussionmentioning
confidence: 99%